Causes of mortality in eagles submitted to the National Wildlife Health Center 1975–2013 - Robin E. Russell; J. Christian Franson (Wildlife Society Bulletin)
ABSTRACT We summarized the cause of death for 2,980 bald eagles (Haliaeetus leucocephalus) and 1,427 golden eagles (Aquila chrysaetos) submitted to the National Wildlife Health Center in Madison, Wisconsin, USA, for diagnosis between 1975 and the beginning of 2013. We compared the proportion of eagles with a primary diagnosis as electrocuted, emaciated, traumatized, shot or trapped, diseased, poisoned, other, and undetermined among the 4 migratory bird flyways of the United States (Atlantic, Mississippi, Central, and Pacific). Additionally, we compared the proportion of lead‐poisoned bald eagles submitted before and after the autumn 1991 ban on lead shot for waterfowl hunting. Trauma and poisonings (including lead poisoning) were the leading causes of death for bald eagles throughout the study period, and a greater proportion of bald eagles versus golden eagles were diagnosed as poisoned. For golden eagles, the major causes of mortality were trauma and electrocution. The proportion of lead poisoning diagnoses for bald eagles submitted to the National Wildlife Health Center displayed a statistically significant increase in all flyways after the autumn 1991 ban on the use of lead shot for waterfowl hunting. Thus, lead poisoning was a significant cause of mortality in our necropsied eagles, suggesting a continued need to evaluate the trade‐offs of lead ammunition for use on game other than waterfowl versus the impacts of lead on wildlife populations. Published 2014. This article is a U.S. Government work and is in the public domain in the USA.